From Law to Logos : reading St. Paul's Epistle to the Galatians - Jordan, Jon R. (Wipf & Stock, 2016)
St. Paul's epistle to the Galatians offers a fascinating window into the life of the Christian church in its earliest days. We see in this letter a pastor guiding his people through questions of salvation, theology, and ethics. The more we read, the more we realize that many of the same questions facing the Galatian Christians continue to face us today: Are we still under the Old Testament Law? What happened to the Law when Jesus came? Who are the people of God? From Law to Logos: Reading St. Paul's Epistle to the Galatians is a primer for reading Galatians for all it is worth. The focus of this book is preparing lay Christians to understand Galatians by reading it as a letter, in its entirety, over and over again. At the end of each chapter, the reader is better prepared to read and study Galatians in its literary, historical, and theological context.